A Pax que vai à luta: um estudo sobre o projeto construção coletiva de espaços e tempos de paz ABCD/SP - Ferreira, Aurimar Pacheco (2011)
The theme of this research referred to an experience conducted by NECA Associação dos Pesquisadores de Núcleos de Estudos e Pesquisas sobre Crianças e o Adolescente, named Collective Construction Project of Spaces and Times of Peace , which occurred along twelve months (January to December/2006) in seven municipalities of the metropolitan region of Sao Paulo, known as Great ABCD, composed by the cities of Santo Andre, Sao Bernardo do Campo, Sao Caetano do Sul, Diadema, Mauá, Ribeirao Pires and Rio Grande da Serra. The operation of the Project was proposed by the Intermunicipal Consortium of the Great ABCD, which represented the juridical collegiate instance of the seven cities, that have been acting in those places for around ten years, as a development agency for the municipalities, affecting the Public Policies and its paths of intermunicipal interactions. The study aimed to investigate the many forms of thematic, the content and the shape of the workshops received by the participants, all them indicated, in their respective cities, by its local municipalities, that was supported by the municipals secretaries of Education, Health, Transport, as well other Public Policies having transversal actuation with the Social Assistances policies. The implementation process of the workshops took twelve months of work, including stages of selection and formation of instructors, work assemblies with the respective municipal secretaries, along with the Greater ABCD Intermunicipal Consortium, local preparation seminaries, mobilization, opening and evaluation of the developed activities. The workshops were accomplished itself between the months of August and December of the year of 2006 and totalized a number of thirty nine, beginning with thirty participants, who were kept in the workshops during four hours a week, during ten weeks. The study presented a cut view about the totality of the workshops and analyses the objective and subjective meanders of such a proposal